The Trypanosoma cruzi Genome Project: Nuclear Karyotype and Gene Mapping of Clone CL Brener - Santos, M.R.M. (1997)
By using improved pulsed field gel electrophoresis conditions, the molecular karyotype of the reference clone CL Brener selected for Trypanosoma cruzi genome project was established. A total of 20 uniform chromosomal bands ranging in size from 0.45 to 3.5 Megabase pairs (Mbp) were resolved in a single run. The weighted sum of the chromosomal bands was approximately 87 Mbp. Chromoblots were hybridized with 39 different homologous probes, 13 of which identified single chromosomes. Several markers showed linkage and four different linkage groups were identified, each comprising two markers. Densitometric analysis suggests that most of the chromosomal bands contain two or more chromosomes representing either homologous chromosomes and/or heterologous chromosomes with similar sizes.